PENANAMAN NILAI-NILAI KEISLAMAN MELALUI KEBIJAKAN HOLISTIK INTEGRATIF KEPALA TK AL-FADLILAH SAMBILEGI KIDUL YOGYAKARTA - Remiswal Remiswal; Arham Junaidi Firman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The objective of this study is to explore the cultivation of Islamic values through the integrative holistic policy of the principal of TK Al-Fadlilah Yogyakarta in improoving school credibility. This study used field study with qualitative approach and program evaluation method. Technique of data collection of this study are observation, documentation and interviews. This study revealed: First, the form of an integrative holistic policy implemented by the principal of TK Al-Fadlilah that covers the healt sector, nutrition sector, educational stimulation sector, care and protection sector. Secondly, the impact of an integrative holistic policy applied by the principal of TK Al-Fadlilah includes both positive and negative impacts. Thridly, the factors that influence the implementation of an integrative holistic policy from principal of TK Al-Fadlilah policy include supporting factors and inhibiting factors. Further, Islamic values are isntilled to students in TK Al-Fadlilah can be grouped into three main components, namely aqidah, worship and morals.